Perceived Organizational Support and Justice on Organizational Commitment through Job Satisfaction In Bengkulu Teachers - Alfiyyah, Saarah; Praningrum, Praningrum (Universitas Islam Kadiri, 2026)
This research investigated the connections between perceived organizational support, organizational justice, and organizational commitment using job satisfaction as a mediating. The study was aimed among teachers at 25 public lower secondary schools in Bengkulu City. Nine schools were selected from this population using cluster random sampling, resulting in 234 valid respondents using a probability-based sampling method. Questionnaires with a five-point likert scale were used to gather data. Partial least squares modeling was used to examine the data using the SmartPLS program. The outcomes demonstrate that commitment is strongly and favorably fixed by job satisfaction. Additionally, it was found that both justice and organizational support significantly contribute to increased job satisfaction. Perceived organizational support had no direct impact on organizational commitment. Its influence only occurred when job satisfaction acted as a mediating aspect, indicating a complete mediation effect. In contrast, organizational justice influences organizational commitment in two ways: directly and indirectly, over job satisfaction. Taken together, these findings emphasize the central role of job satisfaction as a key connecting factor through organizational justice and organizational support shape teachers commitment to their organization.